Advantages Of Explanating Protein Denaturation To Students Through A Virtual Laboratory - Kamalova, Yakutkhan Bahodirovna (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2025)
This paper analyzes the benefits of explaining the process of protein denaturation to students through a virtual laboratory. Virtual laboratories make the educational process more effective and interactive, which makes it easier to understand complex processes. In particular, the ability to visually demonstrate and conduct experiments on microscopic processes such as protein denaturation deepens students’ understanding. The article discusses the advantages of the virtual laboratory over traditional classes, such as visibility, security, cost reduction, and practical application of knowledge. At the same time, the role of virtual laboratories in the development of students’ theoretical knowledge and practical skills is highlighted.